After all [videorecording (DVD)] - Bryant, Jack; Christensen, Erika, 1982-; Miller, Penelope Ann; Muhammad, Kiara, 1998-; Gilford, Zach, 1982-; O'Malley, Mike, 1966- (Brainstorm Media, 2026)
When Ellen returns home to care for her ailing mother and estranged teenage daughter, three generations of women struggle to connect and find the courage to forgive.